K-State Research and Extension 2020 Annual Report - Minton, Ernest J. (My University, 2020)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2020, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
RPT102_2020_01
Keywords: RPT102; Administrative and Research Reports; legislature